Ifrs Versus Cz Gaap: Influence of Construction Contracts on Financial Indicators - Havlová Kristýna (International Journal of Entrepreneurial Knowledge, 2015)
In 2009, 117 countries all over the world allowed to prepare financial statements according to International Financial Reporting Standards (IFRS) including the Czech Republic. Between Czech General Accepted Accounting Principles (CZ GAAP) and IFRS are some differences involving reporting of noncurrent fixed assets, leasing, construction contracts etc. Using different accounting procedure we can get different value of assets and assets are one component that is used to calculate the financial performance indicators. Those indicators are then used by investors to assess the financial performance of companies and the application of IFRS instead of CZ GAAP can lead to distinct presentation of enterprise performance. In this paper we examine the influence of construction contract reporting using IFRS and CZ GAAP on financial indicators. IFRS leads to more stable development during the period when the project is in progress. In the last year when the project is finished the figures of both ratios (ROA and Z-score) are getting worse which is due to the lower percentage of the construction that is built in this year.